1995
DOI: 10.1051/lait:199512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free fatty acids on propionic acid bacteria

Abstract: Summary -The seasonal variations in milk fat composition, especially du ring the grazing period, often lead to poor eye formation in Swiss-type cheese. The influence of free fatty acids on the grow1h and metabolism of the dairy propionibacteria has been studied in this work. Linoleic (C 1B : 2 ), laurie (C 12 : 0 ), myristic (C14:0) and oleic acids (C1B:1) inhibited the growth and acid production of P treudenreichii subsp shermanii in the reference medium. The antibacterial activity of Iinoleic acid can be ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 41 publications
10
39
0
Order By: Relevance
“…The growth stimulation property of Tween-80 and its properties of neutralization of the antimicrobial effect of fatty acids have been well demonstrated in the past (Dubos 1947;Ledeoma et al 1977;Baker et al 1983;Cummins and Johnson 1986). Furthermore, the presence of proteins can also counteract the inhibition of fatty acids (Dubos 1947;Boyaval et al 1995). The results observed in this study thus concur with the opinion that the presence of certain surface active substances, such as Tween-80 or proteins, plays an important role in the recovery of inhibitory effects of free linoleic acid on the growth of propionibacteria and hence, the production of CLA.…”
Section: Discussionsupporting
confidence: 89%
“…The growth stimulation property of Tween-80 and its properties of neutralization of the antimicrobial effect of fatty acids have been well demonstrated in the past (Dubos 1947;Ledeoma et al 1977;Baker et al 1983;Cummins and Johnson 1986). Furthermore, the presence of proteins can also counteract the inhibition of fatty acids (Dubos 1947;Boyaval et al 1995). The results observed in this study thus concur with the opinion that the presence of certain surface active substances, such as Tween-80 or proteins, plays an important role in the recovery of inhibitory effects of free linoleic acid on the growth of propionibacteria and hence, the production of CLA.…”
Section: Discussionsupporting
confidence: 89%
“…However, it appears to be in contrast of Jiang et al [13], who reported that the free linoleic acid in media inhibits the growth of propionibacteria, and hence, CLA production; and suggested that the conversion of free linoleic acid to CLA might be a detoxiWcation mechanism by bacteria. Kim and Liu [16] also reported an optimal concentration of sunXower oil in whole milk at the rate 0.1 g/L and beyond 0.2 g/L has no eVect on CLA production, which was in agreements with the antimicrobial eVect of free linoleic acid on propionic acid bacteria by Boyaval et al [4] and Jiang et al [13]. In present study, when L. viridescens and L. lactis that have the tendency of producing higher CLA with increased sunXower oil, were compared, the latter was found to be better.…”
Section: Resultssupporting
confidence: 77%
“…The high degree of propionic acid fermentation of VZ3 cheeses was certainly related to the higher pH value of these cheeses at the end of pressing [26], and a possible relationship with green maizebased feed is difficult to explain. It is also possible that there was an inhibitory effect of long chain unsaturated fatty acids, found in greater proportions in M milks, on propionic acid bacteria [10].…”
Section: Volatile Compounds In Cheesementioning
confidence: 99%